A phase 2 open-label study of cemiplimab in patients with advanced cutaneous squamous cell carcinoma (EMPOWER-CSCC-1): Final long-term analysis of groups 1, 2, and 3, and primary analysis of fixed-dose treatment group 6 - Hughes, Brett G.M.; Guminski, Alexander; Bowyer, Samantha; Migden, Michael R.; Schmults, Chrysalyne D.; Khushalani, Nikhil I.; Chang, Anne Lynn S.; Grob, Jean Jacques; Lewis, Karl D.; Ansstas, George; Day, Fiona; Ladwa, Rahul; et al. (Journal of the American Academy of Dermatology, 2024)
Background: In the phase 2 EMPOWER-CSCC-1 study (NCT02760498), cemiplimab demonstrated antitumor activity against metastatic cutaneous squamous cell carcinoma (mCSCC) and locally advanced cutaneous squamous cell carcinoma (laCSCC). Objectives: To report final analysis of weight-based cemiplimab in mCSCC and laCSCC (groups 1 and 2), fixed-dose cemiplimab in mCSCC (group 3), and primary analysis of fixed-dose cemiplimab in mCSCC/laCSCC (group 6). Methods: Patients received cemiplimab (3 mg/kg intravenously every 2 weeks [groups 1 and 2]) or cemiplimab (350 mg intravenously [groups 3 and 6]) every 3 weeks. The primary end point was objective response rate (ORR). Duration of response (DOR) and progression-free survival (PFS) are presented per protocol, according to post-hoc sensitivity analyses that only include the period of protocol-mandated imaging assessments. Results: At 42.5 months, ORR for groups 1-3 (n = 193) was 47.2%, estimated 12-month DOR was 88.3%, and median PFS was 26.0 months. At 8.7 months, ORR for group 6 (n = 165 patients) was 44.8%; median DOR and median PFS were not reached. Serious treatment-emergent adverse event rates (grade ≥3) were groups 1-3: 31.1% and group 6: 34.5%. Limitations: Nonrandomized study, nonsurvival primary end point. Conclusion: EMPOWER-CSCC-1 provides the largest prospective data on long-term efficacy and safety for anti-programmed cell death-1 therapy in advanced CSCC.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Adult; advanced cutaneous squamous cell carcinoma; Aged; Aged; 80 and over; Antibodies; Antibodies; Monoclonal; Humanized / pharmacology; Antibodies; Monoclonal; Humanized / therapeutic use; Carcinoma; Carcinoma; Squamous Cell / pathology; cemiplimab; cemiplimab; clinical trials; Female; fixed dose; Follow-Up Studies; Humanized; Humans; immunotherapy; Male; Middle Aged; Monoclonal; skin cancer; skin neoplasms; Skin Neoplasms / drug therapy; Skin Neoplasms / pathology; Squamous Cell / drug therapy; Treatment Outcome